Influence of Genetic Polymorphisms of Tumor Necrosis Factor Alpha and Interleukin 10 Genes on the Risk of Liver Cirrhosis in HIV-HCV Coinfected Patients. - Sara Corchado; Mercedes Márquez; Montserrat Montes de Oca; Paula Romero-Cores; Clotilde Fernández-Gutiérrez; José-Antonio Girón-González (PLoS ONE, 2013)
OBJECTIVE Analysis of the contribution of genetic (single nucleotide polymorphisms (SNP) at position -238 and -308 of the tumor necrosis factor alpha (TNF-α) and -592 of the interleukin-10 (IL-10) promotor genes) and of classical factors (age, alcohol, immunodepression, antirretroviral therapy) on the risk of liver cirrhosis in human immunodeficiency (HIV)-hepatitis C (HCV) virus coinfected patients. PATIENTS AND METHODS Ninety one HIV-HCV coinfected patients (50 of them with chronic hepatitis and 41 with liver cirrhosis) and 55 healthy controls were studied. Demographic, risk factors for the HIV-HCV infection, HIV-related (CD4+ T cell count, antiretroviral therapy, HIV viral load) and HCV-related (serum ALT concentration, HCV viral load, HCV genotype) characteristics and polymorphisms at position -238 and -308 of the tumor necrosis factor alfa (TNF- α) and -592 of the interleukin-10 (IL-10) promotor genes were studied. RESULTS Evolution time of the infection was 21 years in both patients' groups (chronic hepatitis and liver cirrhosis). The group of patients with liver cirrhosis shows a lower CD4+ T cell count at the inclusion in the study (but not at diagnosis of HIV infection), a higher percentage of individuals with previous alcohol abuse, and a higher proportion of patients with the genotype GG at position -238 of the TNF-α promotor gene; polymorphism at -592 of the IL-10 promotor gene approaches to statistical significance. Serum concentrations of profibrogenic transforming growth factor beta1 were significantly higher in healthy controls with genotype GG at -238 TNF-α promotor gene. The linear regression analysis demonstrates that the genotype GG at -238 TNF-α promotor gene was the independent factor associated to liver cirrhosis. CONCLUSION It is stressed the importance of immunogenetic factors (TNF-α polymorphism at -238 position), above other factors previously accepted (age, gender, alcohol, immunodepression), on the evolution to liver cirrhosis among HIV-infected patients with established chronic HCV infections.